2017
DOI: 10.12659/msm.904710
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathogenesis and Biomarkers of Kidney Cancer-Related Stroke

Abstract: BackgroundStroke risk and stroke recurrence are increased in cancer patients, but the pathogenesis and biomarkers of kidney cancer-related stroke (KCS) are generally unclear. The aim of the present research was to investigate the pathogenesis and plasma biomarkers of kidney cancer-related stroke.Material/MethodsA retrospective review was conducted on acute stroke patients with kidney cancer (KC) who were admitted to the hospital between January 2006 and December 2015. A total of 106 patients with KCS (active K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…First, previous studies have demonstrated that cancer-related ischemia may occur after or before the diagnosis of cancer. [12][13][14] In the present study, a similar finding was also revealed in patients with ECIS, indicating that some measures should be taken to prevent ischemic stroke when the diagnosis of EC is obtained or when diagnosing the etiology of a cryptogenic ischemic stroke EC. Second, previous studies found that the clinical features of cancer-related ischemic stroke included elevated plasma DD levels and multiple ischemic lesions distributed in different cerebral arterial territories.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, previous studies have demonstrated that cancer-related ischemia may occur after or before the diagnosis of cancer. [12][13][14] In the present study, a similar finding was also revealed in patients with ECIS, indicating that some measures should be taken to prevent ischemic stroke when the diagnosis of EC is obtained or when diagnosing the etiology of a cryptogenic ischemic stroke EC. Second, previous studies found that the clinical features of cancer-related ischemic stroke included elevated plasma DD levels and multiple ischemic lesions distributed in different cerebral arterial territories.…”
Section: Discussionsupporting
confidence: 84%
“…This was a retrospective study of patients with ECIS from January 2011 to December 2020 at The First Affiliated Hospital of Guangxi Medical University, The Second Affiliated Hospital of Guangxi Medical University, The Ninth Affiliated Hospital of Guangxi Medical University, Fusui County People's Hospital, Wuzhou Red Cross Hospital, Cenxi People's Hospital and The Wuming Hospital of Guangxi Medical University. Based on a previous definition of cancer-related ischemic stroke, [12][13][14] we defined ECIS as acute ischemic stroke in patients with active EC and without conventional stroke risk factors. In the present study, we defined the conventional stroke risk factors as the presence of hypertension, diabetes, hyperlipidemia, atrial fibrillation, valvular heart disease, and cerebral artery stenosis.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in our previous studies. 7,9 Increased levels of serum CA125, a type of mucin that is secreted by the cancer cell, were found to be related to hypercoagulability ischemic stroke in patients with cancer. 25 Moreover, autopsy experiments confirmed that there were mucin components that were secreted by cancer cells in the blood vessels, and they were thromboembolic in patients with cancer and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that the occurrence of CRIS was related to independent risk factors that were derived from serum, and the independent risk factors for CRIS are heterogeneous because they have different pathological types. [7][8][9] It was suggested that the characteristics of specific pathological types of CRIS risk factors may identify CRIS and may even predict its occurrence. Bladder cancer is the tenth most frequent cancer worldwide and the most common urinary tract malignancy.…”
Section: Introductionmentioning
confidence: 99%